COUPLED VERTICAL – TORSIONAL AND LATERAL FREE VIBRATION OF THIN-WALLED CURVED BEAM (Journal of Engineering, 2010)
This study is concerned with the derivation of differential equation of motion for the free coupled vertical – torsional and lateral vibration of opened thin-walled curved beams. The curved beam to be considered in this study is of isotropic opened thin – walled (I) section with equal top and bottom flanges. The derivation depends on Hamilton's principle which required finding the potential and kinetic energy of the curved beam section due to internal stresses and all types of movements (Vertical,Torsional and Lateral) .The effect of restrained warping displacement is also considered in this study. Three differential equations are derived for vertical, torsional and lateral movement .and approximate solutions are developed by using the method of multiple scale via a perturbation technique. The resulting natural frequencies and modes for vertical , torsional and lateral movements are compared with those calculated by using finite element approach ( STAAD Pro. 2007 ) and with the results other studies.